Meshing Characteristic Analysis of the Gear Rack Drilling Rig Hoisting System - Lei Na; Chang Yulian; Bian Cheng; Ren Fushen (Jixie chuandong)
The gear rack drilling rig hoisting system adopts statically indeterminate structure design,in the process of drill-down and lifting,the loading asymmetry influences the synchronism of gear rack meshing movement.Therefore,it is very important to study the meshing characteristic of gear rack in the case of asymmetric loading.The meshing synchronism of gear rack in cases of different types of loading is analyzed with the gear as the research object based on finite element analysis of gear rack meshing through ABAQUS and by the use of joint simulation method of ADAMS and Solid Works,and intensity checking is conducted on each gear.Through calculation and analysis,that force of gear partial to asymmetric loading is greater than that of another side,but the difference is within tolerance.Taking fatigue factor into account,it is required to increase gear strength.